Medication Adherence to Antiretroviral Therapy Among Patients Visiting Antiretroviral Therapy Center at Tribhuvan University Teaching Hospital, Kathmandu, Nepal - Sharma, S; Khadga, P; Dhungana, GP; Chitrakar, U (Kathmandu University Medical Journal, 2014)
Background Although antiretroviral therapy has limited efficiency, patients should take multiple drugs in combination in prescribed time for lifelong and they should also require specific food and fluid restriction. Due to these and other factors patients may discontinue their medication and therefore face significant challenges in adherence. Objectives To assess factors associated with non-adherence among people living with HIV receiving the antiretroviral therapy. Methods Between July 2011 to January 2012, a cross sectional survey was conducted among patients visiting HIV/AIDS unit, Tribhuvan University Teaching Hospital for therapy. After taking informed consent, a pre-structured questionnaire was filled up and data were entered into SPSS 11.5 system and analyzed. Results Of the 100 studied subjects, 61 (61.0%) were male and 39 (39%) were female. Adherence was found to be 79%. The major barrier to adherence was reported to be simply forgetfulness (33.3% of those non adherents). Non adherence was significantly associated with types of family (X2 value, 7.11), smoking (X2 value, 5.44) and alcoholic habit (X2 value, 5.69) but not with gender (X2 value, 2.57). Besides this, poor economic status, and attendance to religious ceremony were reported to be major obstacles to adherence. Conclusion Adherence at this center was found to be only satisfactory. Forgetfulness was reported to be the major cause of non adherence. Persons living in joint family and those with alcoholic and /or smoking habit were more likely to miss the pills. It can be recommended that effective counseling, moral/financial support for HIV/AIDS patients may increase their adherence. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11027 Kathmandu University Medical Journal Vol.11(1) 2013: 50-53